Blessed are the Meek for they Shall Inherit the Earth - Manns, F. (Liber Annuus, 2000)
Abstract Blessed are the meek, for they shall inherit the land. The second beatitude is a quotation of Ps 37. To understand the meaning of the beatitude it is necessary to verify how the pluralistic Judaism of the first century read Ps 37. In the Apocalyptic milieu, in Qumran Pesher, in hellenistic Judaism and even in Pharisaic texts Psalm 37 had a symbolic meaning. The Land was symbol of wisdom, eternal life and heaven. Matthew's Gospel is closer to rabbinic Judaism than to the other trends of Judaism. Insisting on the future: ´They shall inherit the land, Jesus gives to the land an eschatological meaning which is close to the Kingdom.